Activation level of vastus medialis muscle in different rehabilitation exercises - Birck, Andressa Dupont; Zaleski, Jonnas da Fontoura; Franke, Rodrigo de Azevedo; Lima, Cláudia Silveira (Acta Fisiátrica, 2016)
Excessive lateralization, which often occurs by the weakening of Vastus Medialis (VM) muscle of the patella, is one of the causes of Patellofemoral Pain Syndrome (PFPS) For prevention and rehabilitation of PFPS, the VM strength is essential. Objective: The aim of the study was to compare the VM activation level in four different exercises used in the prevention and rehabilitation of PFPS that are isometric knee extension at 30° and 60° and isometric squat at 60° with or without hip adduction. Methods: A sample of 14 sedentary healthy subjects, aged between 20 and 40 years was included. The EMG signal of VM muscle was collected during Maximal Voluntary Isometric Contraction with duration of five seconds for each exercise. From the captured EMG signal, a period of three seconds was cut and thereafter the Root Mean Square value for each exercise was obtained. Results: The results showed that there was significantly greater activation in VM extension exercises compared to squat exercises. However, there was no significant difference between the two extension exercises, as well as between squat exercises. Conclusion: It can be concluded that the best exercises to maximize the activation of the VM are the isometric knee extension, regardless of the rated angle, since they have greater VM activation level, essential for the prevention and rehabilitation of PFPS